2013
DOI: 10.4081/jae.2013.s2.e71
|View full text |Cite
|
Sign up to set email alerts
|

The RHEA-project robot for tree crops pesticide application

Abstract: The sustainable use of pesticide and the need of a renewed integrated system of agricultural knowledge and management, focus the designing of the EU FP7 RHEA Project. The objectives are the design, development, and testing of a new automatic generation of robotic systems to perform field operations for the sustainable crop management. The project affects three case study: chemical, physical, mechanical and thermal effective weed management in maize and wheat cultivations and chemical pesticide management in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Gil et al (2007, 2013) used ultrasonic sensors as well and reported a saving of pesticide ranging between 12.5% and 31.4% for their system, depending on the volume of the canopy. Vieri et al (2013) used in the RHEA‐project a set‐up with eight ultrasonic sensors and eight movable nozzles and could save up to 50% of product. Another precision spraying system that can autonomously navigate through an orchard as well is called Global Unmanned Spray System (GUSS; GUSS, 2019).…”
Section: Sprayingmentioning
confidence: 99%
“…Gil et al (2007, 2013) used ultrasonic sensors as well and reported a saving of pesticide ranging between 12.5% and 31.4% for their system, depending on the volume of the canopy. Vieri et al (2013) used in the RHEA‐project a set‐up with eight ultrasonic sensors and eight movable nozzles and could save up to 50% of product. Another precision spraying system that can autonomously navigate through an orchard as well is called Global Unmanned Spray System (GUSS; GUSS, 2019).…”
Section: Sprayingmentioning
confidence: 99%
“…Each nozzle has an associated ultrasonic sensor that turns on (off) the nozzle if it detects (does not detect) an object in front of the working range of the nozzle. In addition, the upper (lower) nozzles move down (up) if they do not detect an obstacle in the working range [ 35 , 36 ]. This implement was used in the RHEA project to spray olive trees; thus, it is assumed that the potential obstacles are the olive tree canopies.…”
Section: Characteristics Of the Fleet To Be Supervisedmentioning
confidence: 99%
“…De igual forma, las tareas de aplicación variable de pulverización y fertilización pueden ajustarse a la variabilidad espacial del volumen de la copa. Se ha desarrollado maquinaria capaz de adaptar su geometría y sus elementos aplicadores al tamaño del cultivo [6] [7]. Incluso nuevas tecnologías como los UAVs [8] se han desarrollado para aplicar en forma de bajos volúmenes en sistemas productivos, lo que permite un ahorro considerable de inputs y un aumento de los retornos económicos para los productores.…”
Section: Introductionunclassified